Chapter Introduzione - Marazzini, Claudio (Proceedings e report, 2021)
This paper is an introduction to the volume, that collects the contributions presented at the 2019 annual Conference of the Associazione Italiana per la Terminologia (Ass.I.Term), hosted at the Accademia della Crusca. This paper aims to present the importance of the reflection that touches the comparison between terminology and lexicography, through which technology and science can show their positive function for the development and growth of the Italian language, helping it to keep up with the times, in an era in which most of the specialized words, in various disciplines, now come only from English.